PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA CANVA SITE TERHADAP KEMAMPUAN BERPIKIR SPASIAL SISWA - Jayati, Ariska Candra; Sukidin; Yushardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the Problem-Based Learning (PBL) model assisted by Canva Site media on the spatial thinking skills of high school students. The problem underlying this study is the low spatial thinking skills of students as seen from their limitations in understanding the relationship between geosphere phenomena in depth. The research method used is a quasi-experimental design with a posttest only control design. The subjects of the study consisted of two classes, namely the experimental class that implemented the PBL model assisted by Canva Site media and the control class that used the PBL model assisted by PowerPoint media.The results showed that students in the experimental class had a higher average posttest score than the control class. The highest posttest score in the experimental class was 100 and the lowest score was 55, while in the control class the highest score was 94 and the lowest score was 50. The One Way ANOVA test showed a significant difference (p < 0.05) between the two classes, indicating that the implementation of PBL assisted by Canva Site has a positive effect on students' spatial thinking skills.The conclusion of this study is that the PBL model assisted by Canva Site media is able to increase student engagement in learning and help them understand spatial concepts more effectively. The application of this model is recommended for use in other geography learning materials with the note that teachers need to prepare learning carefully so that the results obtained are optimal.